Crystallization of amorphous Hf100-xCux alloys - Mendoza Zélis, Luis Alejandro (1989)
The crystallization of Hf100−xCux (x=33,44,50,59) amorphous alloys was studied by the TDPAC technique. The different stages in the transformation towards equilibrium were investigated through the evolution of the quadrupole perturbation after thermal annealings. The crystallization kinetics of Hf67Cu33 and Hf56Cu44 was analyzed using the Johnson-Mehl-Avrami equation. General trends in the crystallization behavior are discussed.